2007
DOI: 10.1002/anie.200604673
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise Synthesis and Coordination Compound of an Inorganic Cryptand

Abstract: Modeled on organics: The inorganic cryptand [P2{O(SiiPr2)2}2{SiMe2(OSiMe2)2}] (see figure; C black, O orange, P red, Si blue) can be synthesized by a stepwise lithiation/silylation process. A first coordination compound of this ligand was obtained from its reaction with Li[Al(ORF)4].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Careful theoretical studies on the basicity of O(SiH 2 Me 2 ) 2 and OEt 2 revealed that the lower electrostatic attraction in siloxanes results from the repulsion between the positively charged Si atoms and Lewis acids [11]. This proceeding has recently been extended on cyclosiloxanes [12], which were previously described as pseudo crown ethers or inorganic crown ethers [13][14][15]. However, the structural analogy to organic crown ethers is poor, since siloxanes feature O atoms linked by -SiMe 2 -rather than -CH 2 CH 2 -.…”
Section: Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…Careful theoretical studies on the basicity of O(SiH 2 Me 2 ) 2 and OEt 2 revealed that the lower electrostatic attraction in siloxanes results from the repulsion between the positively charged Si atoms and Lewis acids [11]. This proceeding has recently been extended on cyclosiloxanes [12], which were previously described as pseudo crown ethers or inorganic crown ethers [13][14][15]. However, the structural analogy to organic crown ethers is poor, since siloxanes feature O atoms linked by -SiMe 2 -rather than -CH 2 CH 2 -.…”
Section: Introductionmentioning
confidence: 90%
“…The Me groups at the Si atoms adopt an approximately staggered conformation with average dihedral angles of 84.2(2) • at Si1/Si2 and 59.8(2) • at Si3/Si4. Worth mentioning is the unusual orientation of Si4: In all hitherto known sila-crown ether complexes, the Si atoms bonded to coordinating O atoms are approximately arranged in plane with the crown ether O atoms [12][13][14][15]18,19,23]. In contrast to this, Si4 is considerably located beneath the mean plane of the coordinating O atoms.…”
Section: Mismatchmentioning
confidence: 99%
See 3 more Smart Citations